Resident consultant versus on call cover on delivery suite: are outcomes better?. (18th April 2012) - Ballal, S; Dawood, F; Scholefield, H
Abstract : The RCOG/NICE recommend increase consultant presence on delivery suite (DS) to improve outcomes and provide better supervision and training. Methods: We conducted an 18 month comparative study to identify if there was a difference in outcomes between resident and on call consultant session in a large tertiary unit. Elective caesarean sections and multiple births were excluded. 5287 term singleton babies were born during consultant sessions and 2810 outside hours. There were no significant differences in age, parity, gestation or number of induced labours between the groups Conclusions: Our findings suggest that fewer second stage C/S are performed in resident sessions, but there is a higher incidence of prolonged second stage (>4hours), PPH and it appears that there are worse neonatal outcomes. However, a significant confounding factor may be that more planned high risk births occur during resident consultant sessions.